2022
DOI: 10.1002/dta.3331
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted doping: The impact of urine contamination of semen

Abstract: The high sensitivity of antidoping detection tests creates the possibility of inadvertent doping due to an athlete's unknowing ingestion of contaminated environmental sources such as dietary supplements, food, or drinks. Recently, athletes denying use of a prohibited substance have claimed that the positive antidoping tests was due to exchange of bodily fluids with a nonathlete partner using a prohibited substance.Measurement of drugs in semen is largely limited to one or very few samples due to the inaccessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Alternatively, minute contaminations of sf with urine in the 48-h sf collection could be considered as glucuronidated metabolites of LGD-4033 predominate in urine. A recent study has shown that human sf can contain small volumes of urine, which is why it cannot be excluded that a fraction of the observed analytes originates from this source [ 36 ]; however, considering the difference in average volumes of human und porcine ejaculate, the percentage of urine potentially introducing metabolites into ejaculate in the present study is presumably low.…”
Section: Resultsmentioning
confidence: 80%
“…Alternatively, minute contaminations of sf with urine in the 48-h sf collection could be considered as glucuronidated metabolites of LGD-4033 predominate in urine. A recent study has shown that human sf can contain small volumes of urine, which is why it cannot be excluded that a fraction of the observed analytes originates from this source [ 36 ]; however, considering the difference in average volumes of human und porcine ejaculate, the percentage of urine potentially introducing metabolites into ejaculate in the present study is presumably low.…”
Section: Resultsmentioning
confidence: 80%
“…Data demonstrating drug concentrations in ejaculate similar to blood plasma could, to some extent and concentration, introduce prohibited substances into urine specimens. In such cases, testing for seminal fluid‐specific proteins in urine would add critical information as to the plausibility of this scenario, accommodated by immunological and/or chromatographic–mass spectrometric methods, 121 and to which level urine contamination into seminal fluid can affect hypothesized situations was identified as another aspect to properly investigate 122 . Moreover, the unexpected occurrence of an AAF due to a medically required blood transfusion to an athlete 6 months prior to the conducted doping control sample collection by follow‐up investigations 123 underlined the complexity as well as the importance of data‐driven result management, which requires continued high‐quality anti‐doping research.…”
Section: Discussionmentioning
confidence: 99%
“…Data demonstrating drug concentrations in ejaculate similar to blood plasma could, to some extent and concentration, introduce prohibited substances into urine specimens. In such cases, testing for seminal fluid-specific proteins in urine would add critical information as to the plausibility spectrometric methods,121 and to which level urine contamination into seminal fluid can affect hypothesized situations was identified as another aspect to properly investigate 122. Moreover, the unexpected occurrence of an AAF due to a medically required blood transfusion to an athlete 6 months prior to the conducted doping control sample collection by follow-up investigations123 underlined the complexity as well as the importance of data-driven result management, which requires continued high-quality anti-doping research.…”
mentioning
confidence: 99%
“…In the recent years, several cases of contamination involving supplements, [3][4][5] contaminated pharmaceuticals, 6 food, 7,8 complex unusual contaminated items, such as tooth paste, 9 and finally during intimate moments 10,11 have been reported.…”
Section: Introductionmentioning
confidence: 99%